Reissner-Mindlin plate theory for elastodynamics - Shen Rong Wu (Journal of Applied Mathematics)
Existence and uniqueness of solution are proved for elastodynamics of Reissner-Mindlin plate model. Higher regularity is proved under the assumptions of smoother data and certain compatibility conditions. A mass scaling is introduced. When the thickness approaches zero, the solution of the clamped Reissner-Mindlin plate is shown to approach the solution of a Kirchhoff-Love plate.